Genetic polymorphism of msp2 in Plasmodium falciparum isolates among asymptomatic malaria infections from two ecological settings in Cameroon - Aline G. Bouopda-Tuedom; Luc Abate; Brice L. Feufack-Donfack; Christelle M. Ngou; Albert N. Bayibeki; Carole E. Eboumbou Moukoko; Lawrence S. Ayong; Antoine Berry; Thierry Lefèvre; Isabelle Morlais; Sandrine E. Nsango (Malaria Journal)
Abstract Background The high genetic diversity of Plasmodium falciparum parasites is one of the challenges for malaria control and elimination in endemic areas. A better knowledge of parasite genotypes circulating in different disease endemic areas could help to optimize local malaria interventions. This study aimed at determining P. falciparum genetic diversity from isolates collected in forest (Mfou) and humid savanna (Tibati) eco-epidemiological settings in Cameroon. Methods Dried blood spots collected from asymptomatic individuals in 2018 and 2019 were used to determine the Plasmodium infection status and distinguish the Plasmodium spp. by real-time PCR. Allelic polymorphism of the msp2 gene was assessed in the P. falciparum positive samples by nested PCR followed by capillary electrophoresis for revelation of the fragment allelic size. Multiplicity of infection (MOI) was defined as the number of coinfecting genotypes within an infection. General linear mixed models were fitted to evaluate the impact of study site, participant age, gender and bed net ownership on genetic diversity. Results Malaria prevalence among the asymptomatic individuals reached 59.2% (876/1480) in Mfou and 63.4% (808/1274) in Tibati. A total of 36 and 42 different msp2 alleles were detected in Mfou and Tibati, respectively. No genetic differentiation was observed between the two study sites. The msp2 IC/3D7 family was the most polymorphic and the most prevalent in both areas. Overall, more than 60% of the isolates had multiclonal infections. The frequency of multiclonal infections and MOI was higher in Mfou (68.9%, MOI = 2.08) than in Tibati (57.29%, MOI = 1.80). In Mfou, a negative correlation was found between MOI and age. Similarly, a gender effect was observed in Mfou, with males having higher MOI than females. Conclusion This study reported high malaria prevalence and a high allelic diversity in the msp2 gene among asymptomatic carriers from two epidemiological settings of Cameroon. Despite results reflects high transmission intensity in both areas, analysis indicated distinct epidemiological patterns in Mfou and Tibati. These findings will provide valuable baseline information to monitor the impact of malaria control measures implemented in these areas.